ABORTION AND ITS INFLUENCING FACTORS: A QUALITATIVE STUDY IN THE DETENTION CENTER - Rini Hendari; Dahlan H Ahmad; Martiningsih Martiningsih (Belitung Raya Foundation, Indonesia, 2018)
Objective: This study was to explore the actions and factors causing abortion, killing and disposal of babies qualitatively in the detention center of Class II B, Raba Bima, West Nusa Tenggara, Indonesia. Methods: This was a descriptive qualitative study with six respondents who were purposively selected. Content analysis was used for data analysis. Member-checking and crosscheck triangulation were performed to ensure the trustworthiness of the data. Results: Findings emerged from data, namely: factors that cause adolescent abortion, killing and disposal of baby (internal factors, family factors and partner factors), the way to do those actions (to take medicine, by the help of health workers, shaman and the nearest person), and behavior after doing abortion, killing and disposal of baby. Conclusion: Understanding the factors affecting abortion, killing and disposal of baby among adolescents and the way how they did them as well as their behavior after all of these activities might help health practitioners to find the strategies to reduce the incidence of unwanted pregnancy which lead to abortion, killing and infant disposal.